Changes in nitrate and nitrite levels of blanched amaranthus during refrigeration storage. - Chew, S. C.; Prasad, K. Nagendra; Yang Bao,; Ismail, Amin (Universiti Kebangsaan Malaysia Publisher, 2011)
Changes in nitrate and nitrite contents (leaves and stem) of Amaranthus gangeticus (AG) and Amaranthus paniculatus (AP), resulting from blanching, storage time (0-4 days), storage temperature (0 and 4ºC), and reheating were analysed. Results showed that fresh AG (1859 ± 7.07 mg/kg) had higher nitrite content than AP (1262 ± 2.12 mg/kg). Nitrites content was 506 ± 2 and 825 ± 3.5 mg/kg for AG and AP, respectively. Reheating and storage times significantly increased the conversion of nitrate to nitrite in AG and AP. Storage at 0 and 4oC exhibited a significant change (P < 0.05) in nitrate and nitrite contents for both samples. Higher nitrite content was found in AP when stored at 4oC and 0oC. The present study indicated that storage time and temperature affected the nitrite contents in blanched AG and AP when stored in low temperatures. Apart from that reheating was also found to increase the formation of nitrite.